ANALISIS KINERJA SAHAM SEBELUM DAN SESUDAH STOCK SPLIT PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Swari, I Gusti Ayu Winda; Wiksuana, I Gusti Bagus (E-Jurnal Manajemen, 2015)
The company’s stock price are too high hard to reach by investors, therefore companies do stock split to more liquid stocks trading. The purpose of this research was to determine the performance of the stock before and after the stock split at the company listed in Indonesia Stock Exchange. This study used a non-participant observation method  to observe the official website of the Stock Exchange ( www.idx.co.id ). The population of this research is the company that do the stock split in 2012-2013. The samples was 20 companies which are taken by census sampling method and the data analysis technique used is paired sample t-test. The final results indicate there are differences stock returns before and after stock split but not significantly.
Keywords: kinerja saham; return saham; stock split